2020
DOI: 10.1097/lgt.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oral Tramadol 50 mg in Reducing Pain During Colposcopy-Directed Cervical Biopsy: A Randomized Controlled Trial

Abstract: Objective The aim of the study was to assess safety and efficacy of 50-mg tramadol in reducing patient-perceived pain during colposcopy. Material and Methods We conducted a randomized double-blind placebo-controlled trial in the colposcopy unit of a tertiary referral hospital, Cairo, Egypt, from April 2018 to October 2018. Our primary outcome was pain during colposcopy-guided ectocervical punch biopsy. Our secondary outcomes were pain during speculum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Music and forced cough during biopsy are simple strategies that have shown to be effective in reducing pain and anxiety at the time of the colposcopy exam [ 24 , 25 , 26 , 27 , 28 ]. Data on oral analgesia (NSAIDs, opioids) prior to or after the colposcopy exam are lacking and mixed [ 29 , 30 ]; however, these may be considered in addition to non-pharmacologic techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Music and forced cough during biopsy are simple strategies that have shown to be effective in reducing pain and anxiety at the time of the colposcopy exam [ 24 , 25 , 26 , 27 , 28 ]. Data on oral analgesia (NSAIDs, opioids) prior to or after the colposcopy exam are lacking and mixed [ 29 , 30 ]; however, these may be considered in addition to non-pharmacologic techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant research had demonstrated that tramadol, rather than other more powerful opioid medications, can also have some desirable postoperative analgesic effects but with fewer side effects. [102][103][104] The Royal College of Anesthetists claims that 67 mg of tramadol offers the same analgesic effective as 10 mg of morphine. 105 Consequently, tramadol is often utilized in low-and middle-income nations.…”
Section: Medicine Shortage and Restrictionmentioning
confidence: 99%
“…Colposcopy is a standard procedure following abnormal cervical cancer screening. All steps of procedure especially colposcopic directed biopsy (CDB) and endocervical curettage (ECC) made pelvic discomfort, pelvic pain, and anxiety (Darweesh et al, 2020;Wittenborn et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The Efficacy of Oral Etoricoxib in Pain Control During Colposcopy-Directed Cervical Biopsy: A Randomized Control Trial prilocaine intracervical injection (Kiviharju et al, 2017) and oral analgesic drugs ibuprofen (Church et al, 2001) and tramadol (Darweesh et al, 2020). The outcomes of pharmacological methods varied in effectiveness to reduce pain during and after colposcopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation